2011
DOI: 10.1007/s00726-011-1193-7
|View full text |Cite
|
Sign up to set email alerts
|

GABA is an effective immunomodulatory molecule

Abstract: In recent years, it has become clear that there is an extensive cross-talk between the nervous and the immune system. Somewhat surprisingly, the immune cells themselves do express components of the neuronal neurotransmitters systems. What role the neurotransmitters, their ion channels, receptors and transporters have in immune function and regulation is an emerging field of study. Several recent studies have shown that the immune system is capable of synthesizing and releasing the classical neurotransmitter GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
161
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(175 citation statements)
references
References 46 publications
(68 reference statements)
5
161
0
2
Order By: Relevance
“…Koutsos et al (2006) observed that lipopolysaccharide (LPS) challenge in chicks resulted in inflammatory immune responses, as indicated by elevated levels of haptoglobin. GABA has some positive effects on cellular immune function, such as activation or suppression of cytokine secretion, modification of cell proliferation and even cell migration (Jin et al 2013). The levels of lipopolysaccharideinduced tumour necrosis factorα and inflammatory cytokines (interleukin (IL)-1β, IL-6) in serum were significantly decreased by GABA at 80 mg/kg under beak-trimming stress as reported by Xie et al (2013).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Koutsos et al (2006) observed that lipopolysaccharide (LPS) challenge in chicks resulted in inflammatory immune responses, as indicated by elevated levels of haptoglobin. GABA has some positive effects on cellular immune function, such as activation or suppression of cytokine secretion, modification of cell proliferation and even cell migration (Jin et al 2013). The levels of lipopolysaccharideinduced tumour necrosis factorα and inflammatory cytokines (interleukin (IL)-1β, IL-6) in serum were significantly decreased by GABA at 80 mg/kg under beak-trimming stress as reported by Xie et al (2013).…”
Section: Discussionmentioning
confidence: 61%
“…It is biosynthesised through the α-decarboxylation of glutamic acid, catalysed by a glutamate decarboxylase (Chung et al 2009). GABA not only plays the role of a principal inhibitory neurotransmitter in the central nervous system, but also exhibits various nutritional and pharmacological functions, such as the induction of diuresis, a blood pressure-lowering effect, promotion of the absorption of metal ions, tranquilising effects, protecting the liver against alcohol damage, and immunomodulatory effects (Omori et al 1987;Oh and Choi 2000;Adeghate and Ponery 2002;Kimura et al 2002;Jin et al 2013).…”
mentioning
confidence: 99%
“…GABA is widely known to be an inhibitory neurotransmitter in brain. However, this molecule can also be found in many organs and can be expressed by the immune system57. GABA is considered to be effective immunomoldulatory molecule and plays an important role in autoimmune diseases such as type 1 diabetes and rheumatoid arthritis57.…”
Section: Discussionmentioning
confidence: 99%
“…However, this molecule can also be found in many organs and can be expressed by the immune system57. GABA is considered to be effective immunomoldulatory molecule and plays an important role in autoimmune diseases such as type 1 diabetes and rheumatoid arthritis57. A recent study of mechanistic aspects of dehydration stress in the American dog tick showed accumulation of GABA in ticks, although its specific role is unknown58.…”
Section: Discussionmentioning
confidence: 99%
“…GABA is present in significant concentrations in the brain matter but also in the cerebrospinal fluid (Tunnicliff & Malatynska, 2003) and, essentially following breaches of the meningeal barrier due to trauma, surgical acts or, more rarely, by diffusion from infected contiguous structures (paranasal sinus or inner ear), P. aeruginosa can invade the central nervous system causing life-threatening infections such as brain abscesses, ventriculitis or meningitis (Mesaros et al, 2007). However, GABA is also present in blood (Petty et al, 1999) where it has immunomodulatory functions (Jin et al, 2011) and, as P. aeruginosa is a major cause of bloodstream infections (van Delden, 2007), the bacterium is exposed to GABA during bacteraemia or septicaemia. With the emergence of multidrug-resistant strains, it is essential to identify the hosts and communication factors capable of modulating the virulence of P. aeruginosa; these should represent new strategies for treatment (Fothergill et al, 2012).…”
Section: Introductionmentioning
confidence: 99%